An autopsy review of five hundred and sixty nine non-traumatic brought in dead patients in Lagos, Nigeria - Francis Adedayo Faduyile; Sunday Sokunle Soyemi; Daniel Ayodele Sanni; Festus Edobor Emiogun; Fadesewa Ibiolagbajosi Osuolale; Kikelomo Ololade Wright (Egyptian Journal of Forensic Sciences, 2018)
Abstract Background There are many cases that present to the emergency room as brought in dead (BID) and in such cases, previous medical history of the deceased is unknown. Many of the medical problems are either preventable or treatable if managed on time. This study is aimed to determine the age, gender and causes of BID. Results This is a 6 year retrospective autopsy study of all BID patients in Lagos State University Teaching Hospital, Ikeja between 1st January 2010 and 31st December 2015. The data were retrieved from the autopsy reports and were analysed using Statistical Package for Social Sciences version 18. Test for statistical significance was set as p < 0.05. There were 1016 BID recorded representing 9.3% of all deaths during the period under study. A total of 569 cases of BID that were analysed in this study after excluding hypertension related deaths. The male to female ratio was 1.37:1. The 4th decade was the predominant age group (22.7%). Cardiovascular (25.5%), Asphyxia related (23.0%), Gastrointestinal tract [GIT] (16.5%) and respiratory (15.1%) were the common system seen. Thromboembolism and haemorrhage, drowning, severe dehydration and tuberculosis were the most common causes of cardiovascular, asphyxia, GIT and respiratory system deaths respectively. Conclusions Cardiovascular system related death was the most common cause of BID with thromboembolism and haemorrhage as major secondary causes. Tuberculosis was the commonest cause of respiratory system death. BIDs are seen more in male than the female gender. There is need for the government to increase the awareness and health seeking behaviour among the populace.